Pengaruh Profitabilitas, Leverage, Struktur Kepemilikan, Pertumbuhan Penjualan Dan Komisaris Independen Terhadap Manajemen Laba (Studi Empiris Pada Perusahaan Industri Barang Konsumsi yang Terdaftar di BEI Tahun 2012-2014) - Fahmie, Arief (Institut Bisnis dan Informatika Kesatuan, 2018)
The purpose of this research is to analyze and explain the effect of profitability, leverage, ownership structure, sales growth and independent commissioner with earnings management of industry consume goods companies that listed in Indonesian Stock Exchange during 2012 up to 2014. Data collection method used is purposive sampling method, which resulted in 34 companies during three years of observation. And the statistical method used is multiple linear regression and performed classical assumption first. The results showed that partially, profitability and ownership structure effect the earnings management, and then leverage, sales growth, and the independent commissioner does not affect the earnings management. While simultaneous, profitability, leverage, ownership structure, sales growth, and independent commissioner affect the earnings management in industry consume goods companies.